Exploring the Antioxidant Potential of Hen Egg White Lysozyme N-acetylmuramide Glycan Hydrolase in Full Fat Mozzarella Cheese - Saleem, Iqra; Gulzar, Nabila; Nadeem, Muhammad (Emirates Journal of Food and Agriculture, 2023)
To explore the antioxidant potential of hen egg white lysozyme N-acetylmuramide Glycan hydrolase in full fat Mozzarella cheese, an experiment was conducted where control sample was brined without the addition of lysozyme; while four samples were brined along with 0.02%;w/v (T1), 0.04%;w/v (T2), 0.06%;w/v (T3) and 0.08%;w/v (T4) lysozyme. The antioxidant potential of hen egg white lysozyme in full fat Mozzarella cheese samples were measured through several methods, including 2, 2-azino-bis (3-ethylbenzothiazoline-6-sulphonic acid assay (ABTS), 2, 2-diphenyl-1-picrylhydrazyl (DPPH) assay, superoxide radical scavenging activity (PMS-NADH system), free fatty acid analysis and lipid peroxidation inhibition assay in a linoleic acid emulsion system. Intensity scale was used to evaluate the sensory characteristics of cheese. The results showed the percentage inhibition for DPPH, ABTS and superoxide anion activity in control sample increased up to 30 days; but decreased afterwards till 40 days of storage However in case of lysozyme treated samples % inhibition increased throughout storage. Free fatty acid % in full fat Mozzarella cheese was affected by lysozyme and storage days. Lipid peroxidation inhibitory activity in α-linoleic acid model system of lysozyme added samples showed lower absorbance at 500 nm showing higher lipid peroxidation inhibition. Furthermore, it was observed that absorbance was decreased till 30 days of storage which increased further upto 40 days storage period. The study showed that addition of lysozyme improved the shelf life and sensory characteristics of full fat Mozzarella cheese. Keywords: Lysozyme, Antioxidants, N-acetylmuramide Glycan Hydrolase, Full fat Mozzarella cheese,